2016
DOI: 10.1159/000442138
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gland Neoplasms in Children and Adolescents

Abstract: Salivary gland neoplasms (SGNs) in children are uncommon. Epithelial SGNs (ESGNs) comprise the majority (95%), with the remaining being mesenchymal SGNs (MeSGNs). Pleomorphic adenoma is the most frequently encountered benign neoplasm, mucoepidermoid carcinoma is the most frequent malignant ESGN, and rhabdomyosarcoma is the most frequent malignant MeSGN. ESGN presents in the second decade, whereas MeSGN presents in the first and second decades. Swelling without pain or neurological signs is the main presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…One‐fifth of the children experienced pain in conjunction with palpable masses, however facial nerve involvement was rare, which is in agreement with previous reviews . Previous reviews note that children experience symptoms of salivary gland masses for at least 8‐12 months prior to diagnosis . Furthermore, with fine needle cytology, there is a risk of misdiagnosing masses as benign tumors, when they are in fact malignant .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One‐fifth of the children experienced pain in conjunction with palpable masses, however facial nerve involvement was rare, which is in agreement with previous reviews . Previous reviews note that children experience symptoms of salivary gland masses for at least 8‐12 months prior to diagnosis . Furthermore, with fine needle cytology, there is a risk of misdiagnosing masses as benign tumors, when they are in fact malignant .…”
Section: Discussionmentioning
confidence: 99%
“…Radomski et al found a lower 5‐year overall survival (∼84%) with adjuvant radiotherapy in children versus surgery as the only treatment modality (∼98%) . However, the authors did not adjust for tumor grade or stage, which is important considering adjuvant radiotherapy is often reserved for highly aggressive or recurrent tumors . Of the seven studies that estimated 5‐year overall survival, four studies had a survival less than 100%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations